2003
DOI: 10.1189/jlb.1102521
|View full text |Cite
|
Sign up to set email alerts
|

Activation by prion peptide PrP106–126 induces a NF-κB-driven proinflammatory response in human monocyte-derived dendritic cells

Abstract: Specific prion peptides have been shown to mimic the pathologic isoform of the prion protein (PrP) and to induce a neurotoxic effect in vitro and in vivo. As monocytic cells are thought to play a role in the transmission and pathogenesis of prion disease, the use of these peptides in regulating monocytic cell function is under intense investigation. In the current study, we characterize the ability of prion peptide PrP(106-126) to activate specific signaling pathways in human monocyte-derived dendritic cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 53 publications
(60 reference statements)
3
24
0
Order By: Relevance
“…Studies have suggested that the TLR4 ligand LPS and fibrillogenic PrP peptides share a common signaling pathway leading to cytokine generation (3,6,46). Immune cells that express TLR4 such as M⌽s, microglia, and DCs are activated by PrP Sc (3,5,6,38,46,64) and are capable of ingesting and degrading PrP Sc (8,12,35,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that the TLR4 ligand LPS and fibrillogenic PrP peptides share a common signaling pathway leading to cytokine generation (3,6,46). Immune cells that express TLR4 such as M⌽s, microglia, and DCs are activated by PrP Sc (3,5,6,38,46,64) and are capable of ingesting and degrading PrP Sc (8,12,35,41).…”
Section: Discussionmentioning
confidence: 99%
“…Immune cells that express TLR4 such as M⌽s, microglia, and DCs are activated by PrP Sc (3,5,6,38,46,64) and are capable of ingesting and degrading PrP Sc (8,12,35,41). During scrapie pathogenesis, bone marrow-derived M⌽s enter the CNS, where they are likely involved in limiting the accumulation and spread of PrP Sc /scrapie agent throughout the brain (50).…”
Section: Discussionmentioning
confidence: 99%
“…NF-kB pathway and proinflammatory cytokines that are capable of activating it have been previously linked to the pathogenesis of prion diseases (Fabrizi et al, 2001;Bacot et al, 2003;Zhou et al, 2008). In the current study, we characterized the ability of prion peptide PrP106-126 to activate NF-kB signaling pathways in mouse macrophage Ana-1 cells.…”
Section: Introductionmentioning
confidence: 92%
“…Monocytes were purified from mononuclear cells by Ficoll-Hypaque sedimentation, followed by countercurrent centrifugal elutriation, as reported. 22,23 Elutriated monocytes were Ն95% viable as determined by trypan blue exclusion and Ն90% CD14 ϩ as determined by flow cytometry analysis of representative samples. Monocytes and not contaminating lymphocytes have been shown to be the effector cell when cells with this degree of purity (95%) are used.…”
Section: Reagents and Cellsmentioning
confidence: 99%